Association of Salivary Cortisol Level and Social Media Networking Usage - T Mohamed Javad, P; A Kadar Bashah, S; Paulraj, P; Chandramohan, M; Sajeesh, P; P Sajna, K; Ketharin, T (International Journal of Engineering and Technology, 2019)
The present study investigates the usage of social media networking behavior among the MAHSA university students by using structured questionnaire. The salivary cortisol levels among the study groups were estimated. In addition, the association between salivary cortisol and the usage of social media networking was also assessed. Saliva samples were obtained twice a day from selected subjects to analyze the cortisol level. Results of the present study indicate that the 11% of the students spend less than one hour on social media, 40.2% uses two to four hours and 46.4% more than four hours daily; whereas, 2% of the study groups are others. The cortisol levels assessed among the male and female study groups showed high cortisol concentration in both morning and evening. The cortisol levels in the morning seen among the male study group ranges from 0.13-5.49 Âµg/dl and the female cortisol level ranges from 1.11-5.72 Âµg/dl. Besides in the evening, the cortisol levels seem to be higher among the study group. The evening cortisol level of male students ranges from 0.06-4.6 Âµg/dl. Whereas in the females, cortisol level ranges 0.263.9 Âµg/dl. The average value of the cortisol concentration in the morning is seen to be higher among the female study group than the male and in the evening the male cortisol concentration is seen to be higher than the females. Results clearly demonstrated that students spending more hours in social media had higher cortisol levels when compared to less hour users. From the present preliminary study, it is clear that there is an association between salivary cortisol level and the usage of social media networking behavior.Â Â Â